Introduction to medical electronics applications - Jennings, D. (London ; Boston : E. Arnold ; Boston : Distributed in the USA by Little, Brown, 1995)
Medical electronics, or more specifically the instrumentation used in physiological measurement, has changed significantly over the last few years. Developments in electronics technology have offered new and enhanced applications, especially in the areas of data recording and analysis and imaging technology. These changes have been accompanied by more stringent legislation on safety and liability. This book is designed to meet the needs of students on the growing number of courses, undergraduate and MSc. It is a concise and accessible introduction offering a broad overview that encompasses the various contributing disciplines.
Chapter 1: Physiology and Anatomy * Chapter 2: Physiological Measurements * Chapter 3: Computing * Chapter 4: Imaging the Theory and the Modalities * Chapter 5: Safety * Chapter 6: Product Liability.
Includes bibliographical references (p. [215]-217) and index.
Keywords: Medical electronics; Biophysics; Diagnostic Imaging -- instrumentation; Electronics; Electronic books